Technology for Good? Tencent’s Corporate Social Responsibility, Institutional Chameleon, and the Future of Platform Economies - Luzhou Li; Zhian Zhang (Social Media + Society)
There have been global regulatory debates and efforts aimed at holding digital platforms accountable for the public interest. Utilizing mixed methods of documentary research and expert interviews, this article examines how the Chinese digital giant Tencent leverages its adaptive capabilities for corporate social responsibility (CSR) initiatives in response to increasingly stringent regulation in China. Specifically, it explores Tencent’s organizational restructuring, including the establishment of the sustainable social value (SSV) division, as well as the accompanying corporate practices and discursive strategies aimed at enhancing its legitimacy. As an exemplar of the “institutional chameleon,” Tencent has deftly navigated regulatory waters through organizational metamorphosis. However, while Tencent’s enhanced CSR initiatives have certainly yielded some social benefits, the SSV initiatives are increasingly emerging as a new business frontier for the company, leveraging its vast infrastructural capacities to capitalize on the very social fabric it purports to support. This underscores the complexities and contradictions inherent in its CSR practices and the significance of the intrinsic logic of digital platforms as a modern business.